Effect of pre-oxidation on the failure mechanisms of EB-PVD thermal barrier coatings with (Ni, Pt)Al bond coats. (December 2021) - Li, S.; Xu, M.M.; Zhang, C.Y.; Bao, Z.B.; Yang, Y.F.; Zhu, S.L.; Wang, F.H.
Abstract: In order to clarify the effect of pre-oxidation for (Ni, Pt)Al bond coat on failure modes of TBCs, cyclic oxidation behavior of thermal barrier coatings system with both pre-oxidized and normal (Ni, Pt)Al bond coats was investigated at 1100 °C. The results indicated that thermal cycling resistance of TBCs was dramatically enhanced by pre-oxidation, where thinner and lower residual stress oxide scale, lighter rumpling of the BC/TGO interface were achieved pre-oxidized. The failure modes of these two TBCs were completely diverse. Besides, the lower oxygen partial pressure effectively enhanced transformation from θ to α-Al2 O3 during pre-oxidation. Highlights: The low oxygen partial pressure can suppress the formation of θ-Al2 O3 and accelerate its transformation to α-Al2 O3 . Pre-oxidation can effectively relief the rumpling of the BC/TGO interface and improve the thermal cycling resistance of TBCs. The intermixed zone (IMZ) formed in N-TBCs modified the interfacial adhesion of YSZ/TGO.